An Assessment of the Spatial Comfort at the Open Piazza of Baiturrahman Mosque, Banda Aceh, Indonesia - Laina Hilma Sari; Izziah Hasan; Erna Meutia (Graduate Program of Syiah Kuala University, 2020)
The Baiturrahman Grand Mosque is well-known as the identity of Banda Aceh town, Indonesia. The extensive renovation was carried out in 2015 to the Mosque, presenting an open piazza coated with glossy white marble replacing the previous greeneries and grass. This change creates a much different thermal sensation of the prior environment. This condition also invites the contrast to respond and define spatial comfort, including thermal and visual comfort. Therefore, this study conducts an assessment of thermal and visual comfort at the open piazza, which was done through field measurements. The outdoor thermal comfort was calculated using the equations proposed by Sangkertadi that are appropriate for the tropics. The visual comfort was examined using the De Boer glare scale. The result shows the discomfort appearance for both thermal and visual comfort. The study gives recommendations, such as planting greeneries, providing more shades for achieving lower outdoor air temperature. Replacing the glossy marble with the diffusing and rough surface will reduce the glare for getting the more acceptable visual comfort against the marbles.